2017
DOI: 10.1007/s00701-017-3322-x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of efficacy between dorsal root entry zone lesioning and selective dorsal rhizotomy for spasticity of cerebral origin

Abstract: DREZL is more effective for reducing spasticity, but is more destructive than SDR. DREZL should be preferred for bed-ridden patients, and SDR for ambulatory patients. Both operations are helpful for improving ambulatory status. Gait improvement was observed only in patients who underwent SDR. Adult patients with spasticity of cerebral origin benefit from SDR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…No change in tone post-SDR was reported in 24.6% (n = 35). Six of 12 publications documented changes in spasticity using the modified Ashworth score (MAS) [8][9][10][11][12][13]. Analysis of adult patients in these publications showed that SDR led to marked reduction in the spasticity of the hip flexors, hip adductors, hamstrings, quadriceps, and gastrocnemius/soleus muscles (Table 3).…”
Section: Efficacy Of Sdr On Managing Spasticity/tonementioning
confidence: 99%
See 1 more Smart Citation
“…No change in tone post-SDR was reported in 24.6% (n = 35). Six of 12 publications documented changes in spasticity using the modified Ashworth score (MAS) [8][9][10][11][12][13]. Analysis of adult patients in these publications showed that SDR led to marked reduction in the spasticity of the hip flexors, hip adductors, hamstrings, quadriceps, and gastrocnemius/soleus muscles (Table 3).…”
Section: Efficacy Of Sdr On Managing Spasticity/tonementioning
confidence: 99%
“…Five publications documented perioperative complications post-SDR (n = 35) [8,11,14,17,18]. Back pain post-SDR was documented in 37.1% (n = 13) of patients.…”
Section: Postoperative Complicationsmentioning
confidence: 99%
“…Dorsal root entry zone lesioning (DREZL) using microsurgical techniques was pioneered by Sitthinamsuwan since the 1970s [49].…”
Section: Technical Advancementsmentioning
confidence: 99%
“…Sitthinamsuwan et al [49] compared the outcomes of patients who underwent SDR for lesions in the dorsal root entry zone with the goal of reducing spasms. They used the modified Ashworth Scale and the Adductor Tone Rating Scale to assess the severity of the spasticity.…”
Section: Technical Advancementsmentioning
confidence: 99%
“…This study showed that MDT has the potential to significantly improve the quality of life of the patients. In 2017, Sitthinamsuwan et al 25 Published a study comparing DREZ lesioning and selective dorsal rhizotomy in fifteen spasticity patients. They concluded that DREZ lesioning is more effective to reduce spasticity, but more destructive than selective dorsal rhizotomy.…”
Section: Surgical Treatmentmentioning
confidence: 99%